Could the Covid-19 pandemic accelerate the uberfication of the university? - Le Grange, L. (South African Journal of Higher Education, 2020)
The COVID-19 pandemic has radically changed our world. All spheres of social life have been affected by the pandemic. Lockdown and other restriction measures have grinded contact tuition to a hold and we are seeing universities pivot to online learning/teaching. Although authentic online teaching/learning may not be realised in this moment of crisis, online teaching/learning is likely to be expanded post-COVID-19. In this article, I explore the possibility that the COVID-19 pandemic could accelerate the uberfication of the university. The concept of “uberfication of the university” was first mooted by Gary Hall (2016). I argue that although uberfication of the university (or its acceleration) is not preordained, the potential for its actualisation is already embedded in our present social, educational and technological situation. Although the possibility exists that the present situation can also be a carrier of alternatives to uberfication, vectors of escape from the latter will depend on the active construction of counter narratives to uberfication. The article thus sounds a cautionary note to universities.